Rebuilding the protective approach. Technological guaranteesand new principles of worker protection in the digital age - Mercader Uguina, Jesús R. (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
The new technological labour guarantism constitutes the logical and historical extension of classical Labour Law into a context radically transformed by digitalisation and artificial intelligence. The source of structural power imbalance is no longer merely the ownership of the means of production, but increasingly the control of data, algorithms, and automated decision-making systems. In response, the text sets out five founding principles: the principle prohibiting the algorithmic reification of the worker, which establishes human dignity as an absolute and non-derogable limit on any AI system; the principle of collective compensation for the structural weakness of individual consent, which transforms collective bargaining into the institutional counterweight to corporate technological power; the principle of preventive or by-design proportionality in algorithmic work management, which places upon the employer the burden of justifying ex ante the necessity and suitability of the system; the principle of actionable transparency in algorithmic management, which demands an explainability that is genuinely useful for the effective exercise of rights and their challenge before the competent authorities; and the principle of real human reserve in automated work management, which requires substantive human oversight that is technically qualified and endowed with genuine authority to oppose and override algorithmic outcomes.